Fungi and fungal interactions in the Rhynie chert: a review of the evidence, with the description of Perexiflasca tayloriana gen. et sp. nov.†. (18th December 2017) - Krings, Michael; Harper, Carla J.; Taylor, Edith L.
Abstract : The Lower Devonian Rhynie chert is one of the most important rock deposits yielding comprehensive information on early continental plant, animal and microbial life. Fungi are especially abundant among the microbial remains, and include representatives of all major fungal lineages except Basidiomycota. This paper surveys the evidence assembled to date of fungal hyphae, mycelial cords and reproductive units (e.g. spores, sporangia, sporocarps), and presents examples of fungal associations and interactions with land plants, other fungi, algae, cyanobacteria and animals from the Rhynie chert. Moreover, a small, chytrid-like organism that occurs singly, in chain-like, linear arrangements, planar assemblages and three-dimensional aggregates of less than 10 to individuals in degrading land plant tissue in the Rhynie chert is formally described, and the name Perexiflasca tayloriana proposed for the organism. Perexiflasca tayloriana probably colonized senescent or atrophied plant parts and participated in the process of biological degradation. The fungal fossils described to date from the Rhynie chert constitute the largest body of structurally preserved evidence of fungi and fungal interactions from any rock deposit, and strongly suggest that fungi played important roles in the functioning of the Early Devonian Rhynie ecosystem. This article is part of a discussion meeting issue 'The Rhynie cherts: our earliest terrestrial ecosystem revisited'.